Religious Authority in the Age of Instagram: Unveiling the Contestation of Islamic Discourses - Syatar, Abdul; Hasyim, Baso; Rahmatullah; Saputra, Andi Tri; M. Ilham (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2024)
This research explores the contestation of Islamic religious authority in the digital space of Instagram, where traditional boundaries of religious interpretation are increasingly challenged by new forms of expression. With the rise of social media, platforms like Instagram have given rise to virtual Muslim communities, or the